(3GdMOjOs - (3HgQGes
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B: (3agPG cJGH eajO efShH dHgQGe hjSei cJGH GdeQjN hcJGH GdMOjO s
(3BNQgG (B:s
(3hdjcf eG OhfGg ef GdYde GdeajO BNQ eG OhfGg ai cJGH GdMOjO hCeG ejRGf GdMOjO aJPcQg eY LedI GdehGRjf hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B226 - (3U(B228s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B115 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs